2018
DOI: 10.1007/s00330-017-5113-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of image quality in abdominal CT: potential dose reduction with model-based iterative reconstruction

Abstract: PurposeTo estimate potential dose reduction in abdominal CT by visually comparing images reconstructed with filtered back projection (FBP) and strengths of 3 and 5 of a specific MBIR.Material and methodsA dual-source scanner was used to obtain three data sets each for 50 recruited patients with 30, 70 and 100% tube loads (mean CTDIvol 1.9, 3.4 and 6.2 mGy). Six image criteria were assessed independently by five radiologists. Potential dose reduction was estimated with Visual Grading Regression (VGR).ResultsCom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 35 publications
4
60
0
Order By: Relevance
“…Images acquired at tube loads 42 mAs and 98 mAs are included in the present assessment as previous evaluation indicated no significant improvement in image quality between 98 mAs and 140 mAs [8]. Twenty-five patients who underwent a clinically indicated non-enhanced abdominal CT were included, and demographic data (age, height, mass) were recorded.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Images acquired at tube loads 42 mAs and 98 mAs are included in the present assessment as previous evaluation indicated no significant improvement in image quality between 98 mAs and 140 mAs [8]. Twenty-five patients who underwent a clinically indicated non-enhanced abdominal CT were included, and demographic data (age, height, mass) were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The diagnostic performance and effect of model-based iterative reconstruction (MBIR) on different aspects of image quality and potential dose reductions has been studied by several peers [8][9][10][11][12]. However, due to increase in image noise, dose reduction impairs the diagnostic confidence as depiction of low-contrast lesions in abdominal imaging is compromised.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…MBIR has been applied in clinical practice; through the analysis of the existing literatures, MBIR can greatly reduce noise and dramatically improve image quality [11][12][13][14][15][16][17][18], so, we evaluated 0.625mm thin slice image quality instead of routine 5mm images (with ASIR40%) to obtain more details. In addition, it has been reported that MBIR can improve the recognition of necrotic lesions in children and is suitable for displaying the density difference of soft tissue [20].…”
Section: Discussionmentioning
confidence: 99%
“…Iterative reconstruction (IR) has been used in the "double low" CT to reduce image noise and to meet the diagnostic requirements and has been applied to CT applications in chest, abdomen, blood vessel and other areas [5][6][7][8][9][10][11]. In addition, relevant studies have shown that the more sophisticated full model-based iterative reconstruction (MBIR) algorithm is more powerful than the adaptive statistical iterative reconstruction (ASIR) in image noise reduction [12][13][14][15][16][17]. So far, most of the "double-low" CT studies have been focused on blood vessel(s) [3,4,6,8], or in adults, and there are only few reports on CECT in children's abdomen, which often requires higher x-ray doses than other body regions [18].…”
Section: Introductionmentioning
confidence: 99%